High-efficiency anti-bending flexible perovskite solar cell and preparation method thereof

By using polyacrylamide aqueous solution to form an adhesion layer in flexible perovskite solar cells, the problem of poor crystallization quality of the perovskite absorption layer is solved, and a flexible perovskite solar cell with efficient bending resistance is achieved, which improves the photoelectric conversion efficiency and mechanical stability.

CN119300602APending Publication Date: 2025-01-10SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411374154.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Flexible perovskite solar cells have accumulated residual stresses and poor crystallization quality due to the perovskite absorption layer grown on the substrate, resulting in increased defects and severe non-radiative recombination, affecting efficiency and mechanical stability.

Method used

Using polyacrylamide aqueous solution as the adhesion layer, a uniformly covered polymer adhesion layer is formed on the flexible substrate by spin coating and heat treatment, which enhances the adhesion between the perovskite absorbing layer and the electron transport layer, and regulates the crystallization of perovskites. Kinetics, release internal stress, and improve the crystalline quality of the perovskite absorbing layer.

Benefits of technology

It significantly improves the crystal quality and photoelectric conversion efficiency of the perovskite absorption layer, inhibits non-radiative recombination, improves the mechanical stability and photoelectric performance of flexible perovskite solar cells, and reaches a photoelectric conversion efficiency of up to 24.02%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300602A_ABST
    Figure CN119300602A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient bending-resistant flexible perovskite solar cell and a preparation method thereof. According to the method, polyacrylamide containing a positive electric center amino group and a negative electric center carbonyl group is introduced between flexible SnO2 and a perovskite absorption layer, on one hand, the crystallization kinetics of the perovskite absorption layer is adjusted, the internal residual stress when the perovskite absorption layer is formed is released, and the crystallization quality of the perovskite absorption layer is remarkably improved; on the other hand, the polyacrylamide can have strong interaction with SnO2 and perovskite respectively, the two functional layers are effectively adhered, the bonding force between the perovskite absorption layer and the electron transport layer is improved, the highest photoelectric conversion efficiency of 24.02% is finally obtained, the synergistic improvement of the photoelectric property and mechanical stability of the flexible perovskite solar cell is realized, and the flexible perovskite solar cell has good application prospects. And further development of the flexible perovskite solar cell in the fields of Internet of Things, intelligent wearing and the like is further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of perovskite solar cells, and in particular relates to a high-efficiency, bending-resistant, flexible perovskite solar cell and a preparation method thereof. Background Art

[0002] In recent years, perovskite solar cells have great application prospects in the optoelectronic field due to their advantages over silicon cells, such as adjustable band gap, simple preparation process, low cost, and rapid improvement in photoelectric conversion efficiency. Flexible perovskite solar cells, due to their unique characteristics of light weight, bendability and high power-to-mass ratio, have great application potential in wearable devices, building integration, and mobile energy systems. However, the residual stress of the perovskite absorber layer grown on a flexible substrate is accumulated and the crystallization quality is poor. This leads to an increase in defects in the flexible perovskite absorber layer and serious non-radiative recombination, resulting in a decrease in the efficiency and mechanical stability of flexible perovskite solar cells.

[0003] Regarding the functional layer interface, the traditional flexible SnO2 and perovskite interface will inevitably produce stress accumulation, resulting in reduced crystallization quality of the perovskite absorption layer, increased defects, and serious non-radiative recombination at the interface. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a high-efficiency, anti-bending flexible perovskite solar cell and a preparation method thereof, so as to solve the problem of stress accumulation in the existing thin film, resulting in reduced crystallization quality of the perovskite absorption layer, increased defects, and serious non-radiative recombination at the interface.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell comprises the following steps:

[0007] Step 1, preparing a SnO2 electron transport layer on a flexible substrate;

[0008] Step 2, spin-coating a polyacrylamide aqueous solution on the SnO2 electron transport layer, and heating after spin-coating to obtain a polyacrylamide film;

[0009] The polyacrylamide aqueous solution is obtained by dissolving polyacrylamide in water and shaking and stirring at room temperature; the concentration of the polyacrylamide aqueous solution is (0.1-0.8) mg / mL;

[0010] Step 3: Spin coating FA on polyacrylamide film 0.92 MA 0.04 Cs 0.04 PbI3 perovskite precursor solution to obtain a perovskite absorber layer;

[0011] Step 4, preparing a Spiro-OMeTAD hole transport layer on the perovskite absorption layer;

[0012] Step 5: Prepare an Au electrode on the Spiro-OMeTAD hole transport layer to obtain a flexible perovskite solar cell.

[0013] A further improvement of the present invention is:

[0014] Preferably, in step 2, during the preparation of the polyacrylamide aqueous solution, the shaking time is 1 to 3 hours.

[0015] Preferably, in step 2, the spin coating speed of the polyacrylamide aqueous solution is 3000-6000 rpm, and the spin coating time is 30-60 s.

[0016] Preferably, in step 2, the heating temperature is 50-100° C. and the heating time is 5-10 min.

[0017] Preferably, in step 2, the polyacrylamide film is heated and then subjected to ultraviolet ozone treatment for 5 to 20 minutes.

[0018] Preferably, in step 3, the concentration of the perovskite precursor solution is 1.2-1.7M.

[0019] Preferably, in step 3, the spin coating speed of the perovskite precursor solution is 6000 rpm, and the spin coating time is 50 s.

[0020] Preferably, in step 4, before preparing the Spiro-OMeTAD hole transport layer on the perovskite absorption layer, a PEAI passivation layer is prepared on the perovskite absorption layer.

[0021] Preferably, in step 2, the spin coating speed of the SnO2 electron transport layer is 4000-6000 rpm, the spin coating time of the SnO2 electron transport layer is 30-50 s, and after spin coating, it is treated on a hot stage at 100-200°C for 30-90 minutes and treated with ultraviolet ozone for 5-20 minutes.

[0022] A high-efficiency, bend-resistant flexible perovskite solar cell prepared by any of the above preparation methods comprises a flexible substrate, a SnO2 electron transport layer, a polyacrylamide film, a perovskite absorption layer, a Spiro-OMeTAD hole transport layer and an Au electrode arranged in sequence from bottom to top.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention discloses a flexible perovskite solar cell with high efficiency and anti-bending property and a preparation method thereof. The method dissolves polyacrylamide in water to obtain a polyacrylamide aqueous solution, and coats the dissolved polyacrylamide aqueous solution on a flexible electron transport layer to prepare a uniformly covered polymer adhesion layer. The polyacrylamide contains a positively charged center amine group and a negatively charged center carbonyl group, wherein the negatively charged center carbonyl group can interact with the SnO2 electron transport layer, and the positively charged center amine group can react with the perovskite absorption layer based on the next layer, so that the perovskite absorption layer of the adhesion layer grows. Due to the strong interaction force between polyacrylamide and lead iodide in the perovskite, the growth of the perovskite grains can be effectively delayed, the film grains of the perovskite absorption layer are uniform, the quality of the perovskite absorption layer is improved, the non-radiative recombination is effectively suppressed, and finally a photoelectric conversion efficiency of up to 24.02% is obtained. On the other hand, polyacrylamide can have a strong interaction with SnO2 and perovskite respectively, effectively adhere to the two functional layers, improve the bonding force between the perovskite absorption layer and the electron transport layer, and the SnO2 and perovskite absorption layer in the flexible device.

[0025] At the same time, the amine group, carbonyl group and long-chain structure on polyacrylamide can adjust the crystallization dynamics of the perovskite absorber layer, release the internal residual stress during the formation of the perovskite absorber layer, and significantly improve the crystallization quality of the perovskite absorber layer. The final prepared flexible perovskite solar cell has excellent photoelectric properties and mechanical stability, which will further promote the further development of flexible perovskite solar cells in the fields of Internet of Things, smart wearables, etc.

[0026] Furthermore, the shaking and storage time of the polyacrylamide aqueous solution should not be too long.

[0027] Furthermore, by limiting the spin coating speed and spin coating time, the thickness of the polyacrylamide adhesion layer formed by spin coating can meet the requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the potential distribution diagram of polyacrylamide prepared by the method described in the examples of the present invention.

[0029] Figure 2 is a Fourier transform infrared spectrum (FTIRS) of a mixture of polyacrylamide and lead iodide prepared by the method described in the examples of the present invention;

[0030] Among them, (a) shows the bending vibration of RCH=CH2; (b) shows the stretching vibration of -NHR;

[0031] (c) The figure shows the stretching vibration of CH2;

[0032] Figure 3This is a comparative X-ray diffraction (XRD) spectrum of a perovskite absorption layer grown based on a polyacrylamide adhesion layer and a traditional perovskite absorption layer grown based on SnO2 prepared by the method described in the example of the present invention.

[0033] Figure 4 A field emission scanning electron microscopy (SEM) comparison diagram of a perovskite absorption layer grown on a polyacrylamide adhesion layer and a conventional perovskite absorption layer grown on SnO2 prepared by the method described in the examples of the present invention;

[0034] Among them, (a) shows the perovskite absorption layer grown on the polyacrylamide adhesion layer; (b) shows the perovskite absorption layer grown based on SnO2.

[0035] Figure 5 This is a comparison diagram of the steady-state fluorescence (PL) of the perovskite absorption layer prepared by the method described in the example of the present invention before and after the introduction of the polyacrylamide adhesion layer.

[0036] Figure 6 This is a comparison chart of the fluorescence lifetime (TRPL) of the perovskite absorption layer prepared by the method described in the example of the present invention before and after the introduction of the polyacrylamide adhesion layer.

[0037] Figure 7 The XRD (GIXRD) comparison spectra of the perovskite absorption layer prepared by the method described in the invention example before and after the introduction of the polyacrylamide adhesion layer at different incident angles;

[0038] Among them, (a) shows the XRD of the perovskite absorption layer at different slight incident angles before the introduction of the polyacrylamide adhesion layer; (b) shows the XRD of the perovskite absorption layer at different slight incident angles after the introduction of the polyacrylamide adhesion layer;

[0039] Figure 8 The perovskite absorption layer 2θ-sin prepared by the method described in the invention example before and after the introduction of the polyacrylamide adhesion layer 2 (Ψ) Fitted spectrum.

[0040] Fig. 9 The mechanical properties of the flexible perovskite solar cell device prepared by the method described in the invention example before and after the introduction of the polyacrylamide adhesion layer. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0042] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0043] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0045] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0046] The first aspect of the present invention discloses a method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell, comprising the following steps:

[0047] Step 1: Clean the PET / ITO flexible substrate: PET / ITO flexible transparent conductive substrate (2.5*2.5cm 2 ), ultrasonically clean the ITO surface with a glass cleaner for 30 minutes, ultrasonically clean the surface with deionized water for 30 minutes each, blow dry with a nitrogen gun, and treat with ultraviolet ozone for 5-20 minutes to remove organic residues on the ITO surface and increase the wettability of the ITO surface.

[0048] Step 2, preparing a SnO2 electron transport layer;

[0049] Treating the PET / ITO flexible substrate with UV-ozone for 5 to 20 minutes;

[0050] On a PET / ITO flexible substrate, a colloidal SnO2 precursor solution is spin-coated at 4000-6000 rpm for 30-50 seconds, placed on a 100-200° C. hot stage for treatment for 30-90 minutes, and subjected to ultraviolet ozone treatment for 5-20 minutes to obtain a SnO2 electron transport layer.

[0051] Step 3, prepare polyacrylamide aqueous solution:

[0052] First, 0.1 mg to 0.8 mg of polyacrylamide is dissolved in 1 mL of aqueous solution to obtain a mixed solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0053] In this process, polyacrylamide uses water as a solvent, so that solid polyacrylamide can be dissolved in water to avoid particles (other types of solvents have not been found to be able to fully dissolve). In the subsequent coating and annealing process, polyacrylamide can form a uniform film to avoid the presence of particles in the film, which will affect the mechanical properties of the flexible device. At the same time, the film can fully react with the SnO2 electron transport layer and the perovskite absorption layer, improve the quality of the perovskite absorption layer, and play an adhesion role.

[0054] Furthermore, during the preparation of the polyacrylamide aqueous solution, the concentration of polyacrylamide will affect the viscosity of the polyacrylamide aqueous solution. As the concentration of the polyacrylamide aqueous solution continues to increase, the viscosity of the polyacrylamide aqueous solution increases, making it difficult to prepare a uniform ultra-thin polyacrylamide film by spin coating, while the rough and thick polyacrylamide intermediate layer is not conducive to carrier transport and extraction at the interface.

[0055] Step 4, preparing a polyacrylamide film;

[0056] The polyacrylamide aqueous solution is spin-coated on the tin oxide electron transport layer at a spin-coating speed of 3000-6000 rpm for 30-60 seconds. The flexible substrate coated with the polyacrylamide aqueous solution is then placed on a hot stage and heated at 50-100° C. for 5-10 minutes, followed by ultraviolet ozone treatment for 5-20 minutes.

[0057] During the heating process, the polyacrylamide aqueous solution can react with the SnO2 electron transport layer.

[0058] Step 5, preparing a perovskite absorption layer;

[0059] Preparation of 1.2-1.7 M FA 0.92 MA 0.04 Cs 0.04PbI3 perovskite precursor solution (solutes are FAI, MAI, CsI, PbI2 and MAPbBr3 crystal powders; solvent is a mixed organic solvent with a volume ratio of DMF:DMSO of 4:1), FA 0.92 MA 0.04 Cs 0.04 The PbI3 precursor solution was stirred for more than 4 hours, and then filtered through a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm to obtain a clear perovskite solution for use;

[0060] The perovskite precursor liquid is evenly coated on the surface of the polyacrylamide adhesion layer, and then the process parameters of spin coating are 6000 rpm for 50 seconds; at the beginning of the spin coating, 800-1200 μL of ether is added to the surface of the perovskite precursor liquid, and the perovskite absorption layer is obtained by placing the perovskite precursor liquid on a hot plate at 100-150°C for 10-30 minutes.

[0061] Step 6: Preparation of PEAI passivation layer. Weigh 5 mg of PEAI and dissolve it in 1 mL of isopropanol. Stir for more than 4 hours to prepare a PEAI perovskite passivation solution. Spin-coat the perovskite passivation solution on the perovskite absorption layer at a speed of 3000-5000 rpm for 30-40 seconds to obtain a PEAI passivation layer.

[0062] Step 7: Preparation of Spiro-OMeTAD hole transport layer. When preparing the hole transport layer solution, 0.90 g of Spiro-OMeTAD needs to be dissolved in 1 mL of chlorobenzene, and 22 μL of pre-configured Li-TFSI solution (520 mg / mL) and 36 μL of tBP solution are added. Stir at room temperature in the dark for 4-6 hours, and then filter with a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm to obtain the Spiro-OMeTAD solution; spin-coat the Spiro-OMeTAD solution on the PEAI passivation layer at a speed of 5000 rpm for 30 seconds to obtain the hole transport layer, and store it in a dry bowl for 4 to 6 hours.

[0063] Step 8, Au electrode evaporation: The oxidized film is transferred into the evaporation chamber and a 60-120 nm thick Au electrode is deposited by thermal evaporation. The effective area of ​​the mask is 0.09 cm 2 .

[0064] Step 9: Use a solar simulator to generate a standard sunlight (AM 1.5G, 100mW / cm 2 ) to measure various parameters such as open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE) under the solar simulator. The scanning range of the solar simulator is 1.5~–0.1V, the delay time is 10~50ms, and the scanning step width is 0.01~0.02V.

[0065] The structure of the perovskite solar cell device in the present invention is sequentially PET / ITO substrate, SnO2 electron transport layer, polyacrylamide adhesion layer, perovskite absorption layer, PEAI passivation layer, Spiro-OMeTAD and Au electrode.

[0066] The present invention introduces polyacrylamide between tin oxide and the perovskite functional layer to form a polymer adhesion layer. The perovskite absorption layer grown based on the adhesion layer has significantly reduced internal residual stress, significantly improved crystallization quality of the perovskite absorption layer, and effectively suppressed non-radiative recombination. The flexible perovskite solar cell finally prepared has excellent photoelectric performance and mechanical stability, which will further promote the further development of flexible perovskite solar cells in the fields of the Internet of Things, smart wearables, etc.

[0067] The following is further described in conjunction with specific embodiments.

[0068] Comparative Example 1

[0069] Step 1: Clean the flexible substrate

[0070] Clean the PET / ITO flexible substrate and place the PET / ITO flexible transparent conductive substrate (2.5*2.5cm 2 ), ultrasonic cleaning with glass cleaning agent for 30 minutes, ultrasonic cleaning with deionized water for 30 minutes each, drying with nitrogen gun, and ultraviolet ozone treatment for 5-20 minutes for standby use, so as to remove organic residues remaining on the ITO surface and increase the wettability of the ITO surface;

[0071] Step 2: Prepare SnO2 colloidal solution

[0072] First, SnO2 and ultrapure water were mixed at a volume ratio of SnO2:H2O=1:2, and stirred at room temperature for 2 hours to obtain a colloidal SnO2 precursor solution at a stirring speed of 300 r / min.

[0073] The PET / ITO substrate was treated with UV-ozone for 12 minutes; the SnO2 precursor solution was kept at 6000 rpm for 30 seconds, placed on a 150°C hot stage for 30 minutes, and treated with UV-ozone for 10 minutes to obtain a SnO2 electron transport layer;

[0074] Step 3, preparation of perovskite absorber layer: Pipette 70 μL of 1.4 M FA 0.92 MA 0.04 Cs 0.04 The PbI3 perovskite precursor solution was evenly coated on the SnO2 electron transport layer; at the beginning of spin coating, 1000 μL of anti-solvent ether was added to the perovskite surface, and then the prepared FA 0.92 MA 0.04 Cs 0.04The PbI3 perovskite absorber layer was annealed and placed on a hot plate at 120°C for 20 minutes.

[0075] Step 4, preparation of hole transport layer, 0.90g of Spiro-OMeTAD was dissolved in 1mL of chlorobenzene, and 22μL of pre-prepared Li-TFSI solution (520mg / mL) and 36μL of tBP solution were added, stirred at room temperature in the dark for 6h, and then filtered with a polytetrafluoroethylene filter membrane with a pore size of 0.45μm. Spiro-OMeTAD solution was obtained; the annealed perovskite absorption layer was cooled to room temperature, and the Spiro-OMeTAD solution was spin-coated on the perovskite substrate at a speed of 5000rpm, 30s to obtain a hole transport layer, which was stored in a dark and dry place for 6 hours.

[0076] Step 5, Au electrode evaporation: The oxidized film is transferred into the evaporation chamber and 80nm thick Au electrode is deposited by thermal evaporation. The effective area of ​​the mask is 0.09cm 2 .

[0077] The comparative example obtains a perovskite solar cell having a structure of a PET / ITO substrate, a SnO2 electron transport layer, a perovskite absorption layer, a PEAI passivation layer, a Spiro-OMeTAD and an Au electrode.

[0078] Example 1

[0079] The invention discloses a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0080] Step 1: Clean the PET / ITO flexible substrate: Place the PET / ITO flexible transparent conductive substrate (2.5*2.5cm 2 ), ultrasonic cleaning with glass cleaning agent for 30 minutes, ultrasonic cleaning with deionized water for 30 minutes each, drying with nitrogen gun, and ultraviolet ozone treatment for 5-20 minutes for standby use, so as to remove organic residues remaining on the ITO surface and increase the wettability of the ITO surface;

[0081] Step 2, prepare SnO2 colloidal solution:

[0082] First, SnO2 and ultrapure water were mixed at a volume ratio of SnO2:H2O=1:2, and stirred at room temperature for 2 hours to obtain a colloidal SnO2 precursor solution at a stirring speed of 300 r / min.

[0083] The PET / ITO substrate was treated with UV-ozone for 12 minutes; the SnO2 precursor solution was spin-coated at 6000 rpm for 30 seconds, placed on a 150°C hot stage for 30 minutes, and treated with UV-ozone for 10 minutes to obtain a SnO2 electron transport layer;

[0084] Step 3, preparation of polyacrylamide adhesion layer.

[0085] First, 0.1 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution. The higher the concentration, the longer the shaking time, but the shaking time should not be too long, otherwise the aqueous solution will gradually solidify.

[0086] Step 4: Spin-coat the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, place the flexible substrate coated with the polyacrylamide aqueous solution on a hot plate, heat at 100° C. for 5 minutes, and then perform UV ozone treatment for 10 minutes.

[0087] Step 5, preparation of perovskite absorber layer: Pipette 70 μl of 1.4 M FA 0.92 MA 0.04 Cs 0.04 The PbI3 perovskite precursor solution was evenly coated on the polymer layer; at the beginning of spin coating, 1000 μL of anti-solvent ether was added to the perovskite surface, and then the prepared FA 0.92 MA 0.04 Cs 0.04 The PbI3 perovskite absorber layer was annealed and placed on a hot plate at 120°C for 20 minutes.

[0088] Step 6, preparation of the hole transport layer, 0.90g of Spiro-OMeTAD needs to be dissolved in 1mL of chlorobenzene, and 22μL of pre-prepared Li-TFSI solution (520mg / mL) and 36μL of tBP solution are added, stirred at room temperature in the dark for 6h, and then filtered with a polytetrafluoroethylene filter membrane with a pore size of 0.45μm. The Spiro-OMeTAD solution is obtained; the annealed perovskite absorption layer is cooled to room temperature, and the Spiro-OMeTAD solution is spin-coated on the perovskite substrate at a speed of 5000rpm, 30s to obtain a hole transport layer, which is stored in a dark and dry place for 6 hours.

[0089] Step 7, Au electrode evaporation: The oxidized film is transferred into the evaporation chamber and 80nm thick Au electrode is deposited by thermal evaporation. The effective area of ​​the mask is 0.09cm 2 .

[0090] The perovskite solar cells obtained in this embodiment and the comparative example were characterized and analyzed, and the following results were obtained:

[0091] Figure 1This is the potential distribution diagram of polyacrylamide prepared by the method described in Example 1. From the figure, it can be seen that the data show that polyacrylamide does have a positively charged central amine group and a negatively charged central carbonyl group.

[0092] Figure 2 This is the Fourier transform infrared spectrum (FTIRS) of the polyacrylamide prepared by the method described in Example 1 before and after mixing with lead iodide. The Fourier transform infrared spectrum has obvious movement under the participation of PbI2, indicating that there is a strong interaction between polyacrylamide and PbI2 in perovskite, which provides a possibility for regulating the crystallization of the perovskite absorption layer.

[0093] Figure 3 The X-ray diffraction (XRD) comparison spectra of the perovskite absorber layer grown on the polyacrylamide adhesion layer prepared by the method described in Example 1 and the perovskite absorber layer grown on SnO2 in the comparative example. Compared with the perovskite absorber layer grown directly on SnO2, the diffraction peak at 14.2° of the optimized film is significantly enhanced, and the half-peak width is reduced, indicating that the crystallization quality of the perovskite absorber layer is significantly improved.

[0094] Figure 4 This is a field emission scanning electron microscope (SEM) comparison of the perovskite absorber layer grown on the polyacrylamide adhesion layer prepared by the method described in Example 1 and the conventional perovskite absorber layer grown on SnO2 in the comparative example. The grain size of the perovskite absorber layer grown on the polyacrylamide is significantly increased, which is consistent with the Figure 3 The XRD test results are consistent.

[0095] Figure 5 This is a steady-state fluorescence comparison diagram of the perovskite absorption layer after the polyacrylamide adhesion layer is introduced and the comparative example prepared by the method described in Example 1. The fluorescence intensity of the perovskite absorption layer grown based on polyacrylamide is significantly lower than that of the perovskite absorption layer directly grown based on the SnO2 film. The quality of the perovskite absorption layer is improved, and non-radiative recombination is suppressed.

[0096] Figure 6 This is a comparison of the fluorescence lifetimes of the polyacrylamide adhesion layer and the comparative perovskite absorption layer prepared by the method described in Example 1. The lifetime of the photogenerated carriers in the perovskite absorption layer is significantly enhanced, which is Figure 5 This corresponds to the PL data, indicating that non-radiative recombination is suppressed in the perovskite absorption layer.

[0097] Figure 7 The XRD (GIXRD) comparison spectra at different incident angles of the polyacrylamide adhesion layer and the comparative perovskite absorption layer prepared by the method described in Example 1 indicate that there is obvious tensile stress in the perovskite absorption layer directly grown based on the SnO2 film, and after the polyacrylamide polymer layer is introduced, the stress is effectively released.

[0098] Figure 8 The polyacrylamide adhesion layer and the comparative perovskite absorption layer 2θ-sin prepared by the method described in Example 1 2 (Ψ) Fitting spectrum. The residual stress of the perovskite absorber layer after optimization was reduced from 132.20MPa to 20.66MPa, which further proves that the introduction of polyacrylamide can effectively release the residual stress of the perovskite absorber layer.

[0099] Fig. 9 The mechanical properties of the perovskite solar cell device with polyacrylamide adhesion layer and the comparative example prepared by the method described in Example 1. After 14,000 bending cycles, the flexible perovskite solar cell device with polyacrylamide can still maintain 86% of the initial efficiency, and the mechanical properties are significantly improved.

[0100] Example 2

[0101] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0102] Step 2, preparation of polyacrylamide adhesion layer:

[0103] First, 0.2 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid; if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0104] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0105] The other steps are the same as those in Example 1.

[0106] Example 3

[0107] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0108] Step 2, preparation of polyacrylamide adhesion layer:

[0109] First, 0.3 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid; if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0110] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0111] The other steps are the same as those in Example 1.

[0112] Example 4

[0113] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0114] Step 2, preparation of polyacrylamide adhesion layer:

[0115] First, 0.4 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid; if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0116] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0117] The other steps are the same as those in Example 1.

[0118] Example 5

[0119] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0120] Step 2, preparation of polyacrylamide adhesion layer:

[0121] First, 0.5 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0122] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0123] The other steps are the same as those in Example 1.

[0124] Example 6

[0125] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0126] Step 2, preparation of polyacrylamide adhesion layer:

[0127] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0128] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0129] The other steps are the same as those in Example 1.

[0130] Example 7

[0131] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0132] Step 2, preparation of polyacrylamide adhesion layer:

[0133] First, 0.7 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0134] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0135] The other steps are the same as those in Example 1.

[0136] Example 8

[0137] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0138] Step 2, preparation of polyacrylamide adhesion layer:

[0139] First, 0.8 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid; if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0140] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0141] The other steps are the same as those in Example 1.

[0142] Example 9

[0143] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0144] Step 2, preparation of polyacrylamide adhesion layer:

[0145] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0146] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 3000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0147] The other steps are the same as those in Example 1.

[0148] Example 10

[0149] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0150] Step 2, preparation of polyacrylamide adhesion layer:

[0151] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0152] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 5000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0153] The other steps are the same as those in Example 1.

[0154] Embodiment 11

[0155] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0156] Step 2, preparation of polyacrylamide adhesion layer:

[0157] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0158] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 6000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0159] The other steps are the same as those in Example 1.

[0160] Example 12

[0161] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0162] Step 2, preparation of polyacrylamide adhesion layer:

[0163] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0164] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot plate, heated at 50° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0165] The other steps are the same as those in Example 1.

[0166] Example 13

[0167] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0168] Step 2, preparation of polyacrylamide adhesion layer:

[0169] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, a viscous colloid is easily formed, and if the shaking time is short, the polyacrylamide is difficult to dissolve completely.

[0170] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot plate, heated at 80° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0171] The other steps are the same as those in Example 1.

[0172] Table 1 Comparison of photoelectric conversion efficiency of perovskite absorption layers on different substrates.

[0173]

[0174]

[0175] Embodiment 14

[0176] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0177] Step 2, preparation of polyacrylamide adhesion layer:

[0178] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid, and if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0179] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot stage, heated at 100° C. for 5 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0180] The other steps are the same as those in Example 1.

[0181] Table 1 is a comparison of the photoelectric conversion efficiency of the perovskite absorption layer on different substrates prepared by the method described in the examples of the present invention. The flexible perovskite solar cell device prepared based on a polyacrylamide solution with a concentration of 0.6 mg / mL has the best efficiency, which is 24.02%.

[0182] Embodiment 15

[0183] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0184] Step 2, preparation of polyacrylamide adhesion layer:

[0185] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid, and if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0186] Step 3, spin-coating the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, the flexible substrate coated with the polyacrylamide aqueous solution was placed on a hot plate, heated at 50° C. for 10 minutes, and then subjected to UV ozone treatment for 10 minutes.

[0187] The other steps are the same as those in Example 1.

[0188] Example 16

[0189] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0190] Step 2, preparation of polyacrylamide adhesion layer:

[0191] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid, and if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0192] Step 3, spin-coat the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, place the flexible substrate coated with the polyacrylamide aqueous solution on a hot plate, heat at 50° C. for 10 minutes, and perform UV ozone treatment for 5 minutes after heating.

[0193] The other steps are the same as those in Example 1.

[0194] Embodiment 17

[0195] The present embodiment provides a high-efficiency, anti-bending, flexible perovskite solar cell and a method for preparing the same, comprising the following preparation steps:

[0196] Step 2, preparation of polyacrylamide adhesion layer:

[0197] First, 0.6 mg of polyacrylamide is dissolved in 1 mL of aqueous solution, and the mixed solution is shaken and stirred at room temperature for 1 to 3 hours until the polyacrylamide particles are completely dissolved to obtain a polyacrylamide aqueous solution; if the shaking time and storage time are too long, it is easy to form a viscous colloid, and if the shaking time is short, it is difficult for the polyacrylamide to dissolve completely.

[0198] Step 3, spin-coat the polyacrylamide aqueous solution on the tin oxide electron transport layer at a spin-coating speed of 4000 rpm for 30 seconds. Then, place the flexible substrate coated with the polyacrylamide aqueous solution on a hot plate, heat at 50° C. for 10 minutes, and perform UV ozone treatment for 20 minutes after heating.

[0199] The other steps are the same as those in Example 1.

[0200] Embodiment 18

[0201] In this embodiment, the concentration of the perovskite precursor solution is 1.2 M, and the remaining parts are the same as those in Embodiment 1.

[0202] Embodiment 19

[0203] In this embodiment, the concentration of the perovskite precursor solution is 1.7 M, and the remaining parts not involved are the same as those in Embodiment 1.

[0204] Embodiment 20

[0205] In this embodiment, the spin coating speed of the SnO2 electron transport layer is 4000 rpm, the spin coating time is 50 s, and after spin coating, it is treated on a hot stage at 100°C for 90 minutes and treated with ultraviolet ozone for 5 minutes.

[0206] Embodiment 21

[0207] In this embodiment, the spin coating speed of the SnO2 electron transport layer is 6000 rpm, the spin coating time is 30 s, and after spin coating, it is treated on a hot stage at 200°C for 30 minutes and treated with ultraviolet ozone for 5 minutes.

[0208] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell, characterized in that: The following steps are involved: Step 1, preparing a SnO2 electron transport layer on a flexible substrate; Step 2, spin-coating a polyacrylamide aqueous solution on the SnO2 electron transport layer, and heating after spin-coating to obtain a polyacrylamide film; The polyacrylamide aqueous solution is obtained by dissolving polyacrylamide in water and shaking and stirring at room temperature; the concentration of the polyacrylamide aqueous solution is (0.1-0.8) mg / mL; Step 3: Spin coating FA on polyacrylamide film 0.92 MA 0.04 Cs 0.04 PbI3 perovskite precursor solution to obtain a perovskite absorber layer; Step 4, preparing a Spiro-OMeTAD hole transport layer on the perovskite absorption layer; Step 5: Prepare an Au electrode on the Spiro-OMeTAD hole transport layer to obtain a flexible perovskite solar cell.

2. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 2, during the preparation of the polyacrylamide aqueous solution, the shaking time is 1 to 3 hours.

3. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 2, the spin coating speed of the polyacrylamide aqueous solution is 3000-6000 rpm, and the spin coating time is 30-60 s.

4. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 2, the heating temperature is 50-100° C. and the heating time is 5-10 min.

5. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 2, the polyacrylamide film is heated and then treated with ultraviolet ozone for 5 to 20 minutes.

6. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 3, the concentration of the perovskite precursor solution is 1.2-1.7M.

7. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 3, the spin coating speed of the perovskite precursor solution is 6000 rpm, and the spin coating time is 50 s.

8. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 4, before preparing the Spiro-OMeTAD hole transport layer on the perovskite absorption layer, a PEAI passivation layer is prepared on the perovskite absorption layer.

9. The method for preparing a high-efficiency, anti-bending, flexible perovskite solar cell according to claim 1, characterized in that: In step 2, the spin coating speed of the SnO2 electron transport layer is 4000-6000 rpm, the spin coating time of the SnO2 electron transport layer is 30-50 s, and after spin coating, it is treated on a hot stage at 100-200°C for 30-90 minutes and treated with ultraviolet ozone for 5-20 minutes.

10. A high-efficiency, anti-bending, flexible perovskite solar cell prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It includes a flexible substrate, a SnO2 electron transport layer, a polyacrylamide film, a perovskite absorption layer, a Spiro-OMeTAD hole transport layer and an Au electrode which are arranged in sequence from bottom to top.

Citation Information

Patent Citations

  • Environment-friendly lead-based perovskite composite material, preparation method and solar cell

    CN113462111A

  • Efficient and stable-air-humidity perovskite solar cell capable of cooperatively improving defects and ion migration

    CN115605029A